Leader Empowering Behaviors and Psychological Empowerment as Perceived by Young Hospital Staff Nurses: A Pilot Study - Ryan Michael Oducado (Jurnal Ners, 2019)
Introduction: Empowerment has become an important concept in nursing that has gained acknowledgment in theories and practice of leadership and management. A positive organization espouses empowerment to attract and retain employees. While it is not new to nursing, there is little published research on empowerment among nurses in the Philippines. This study aimed to measure young staff nurses' perception of leader empowering behaviors and psychological empowerment. Methods: This study used a cross-sectional survey design participated by 44 conveniently chosen staff nurses in a private teaching and training hospital in Iloilo City, Philippines. The participants were asked to answer 5-point Likert scale questions utilizing adopted instruments. Descriptive and non-parametric statistical stools were used with Mann-Whitney U test to determine differences and Spearman's rank correlation to establish relationship between variables. Results: Overall, young staff nurses perceived their leaders' behaviors to be highly empowering (M=3.89). Staff nurses also had a high level of psychological empowerment (M=4.07). Leader empowering behaviors was significantly related to staff nurses' perception of psychological empowerment (p=.001). Staff nurses' level of psychological empowerment were significantly different in terms of employment status (p=.020) and years of work experience (p=.014). Conclusion: This study highlights the positive influence of the empowering behaviors of leaders in enhancing staff nurses' level of psychological empowerment. It is vital for nurse managers to continually demonstrate leadership behaviors that empower staff nurses at the unit level.
Keywords: 330; empowerment; leadership; nursing; psychological empowerment; leader empowering behaviors; leadership behaviors